Risk Factors and Clinical Outcomes of Cognitive Impairment in Diabetic Patients Undergoing Peritoneal Dialysis - Xuan Huang; Chunyan Yi; Meiju Wu; Yagui Qiu; Haishan Wu; Hongjian Ye; Yuan Peng; Xi Xiao; Jianxiong Lin; Xuqing Yu; Xiao Yang (Karger Publishers, 2021)
Introduction: Cognitive impairment (CI) is common in patients with CKD or diabetes mellitus (DM). However, the relevance between DM and CI in diabetic patients undergoing peritoneal dialysis (PD) has not been clearly established. This study aimed to explore the role of DM in CI, the association of glycemic control with CI, and clinical outcomes of CI in diabetic PD patients. Methods: Continuous ambulatory PD (CAPD) patients followed up in our PD center between 2014 and 2016 were enrolled. The participants were followed until an endpoint was reached or December 2017. Demographic data and clinical characteristics were collected, and laboratory parameters were measured. The Montreal Cognitive Assessment (MoCA) was used to evaluate global cognitive function, and a score of <26 was considered to indicate CI. A propensity score matching according to age, gender, and mean arterial pressure was conducted between the DM and non-DM groups. Results: A total of 913 CAPD patients were enrolled, of whom 186 (20.4%) had diabetes. After appropriate matching, 175 patients in the DM group and 270 patients in the non-DM group were included. Patients with diabetes had a higher prevalence of CI and lower scores for visuospatial/executive function, naming, language, delayed recall, and orientation. Higher HbA1c (odds ratio [OR], 1.547; 95% confidence interval [95% CI], 1.013-2.362) and cardiovascular disease (CVD; OR, 2.926; 95% CI, 1.139-7.516) significantly correlated with a risk of CI in diabetic patients. During a median of 26.0 (interquartile range 13.5-35.6) months of follow-up, diabetic patients with CI demonstrated a significantly lower survival rate than those without CI, and CI was an independent risk factor for mortality after adjustment (hazard ratio, 7.224; 95% CI, 1.694-30.806). However, they did not show worse technique survival or higher peritonitis rate than patients without CI. Conclusions: HbA1c and CVD are independent risk factors for CI in diabetic patients undergoing CAPD, and CI is independently associated with a higher risk of mortality.